3H-1, 2-benzoxathiepine 2, 2-dioxides: a new class of isoform-selective carbonic anhydrase inhibitors. (1st January 2017) - Pustenko, Aleksandrs; Stepanovs, Dmitrijs; Žalubovskis, Raivis; Vullo, Daniela; Kazaks, Andris; Leitans, Janis; Tars, Kaspars; Supuran, Claudiu T.
Abstract: A new chemotype with carbonic anhydrase (CA, EC 4.2.1.1) inhibitory action has been discovered, the homo-sulfocoumarins (3 H -1, 2-benzoxathiepine 2, 2-dioxides) which have been designed considering the (sulfo)coumarins as lead molecules. An original synthetic strategy of a panel of such derivatives led to compounds with a unique inhibitory profile and very high selectivity for the inhibition of the tumour associated (CA IX/XII) over the cytosolic (CA I/II) isoforms. Although the CA inhibition mechanism with these new compounds is unknown for the moment, we hypothesize that it may be similar to that of the sulfocoumarins, i.e. hydrolysis to the corresponding sulfonic acids which thereafter anchor to the zinc-coordinated water molecule within the enzyme active site.